Thermophysical behaviour of LULC surfaces and their effect on the urban thermal environment - Hamoodi, M.; Corner, R.; Dewan, Ashraf (Taylor & Francis Asia Pacific (Singapore), 2017)
© 2017 Mapping Sciences Institute, Australia and Surveying and Spatial Sciences Institute The aims of this study are to investigate the thermophysical behaviour of various urban land use/land cover (LULC) surfaces in an urban environment, and to examine the relationship between field measurements and remotely sensed data. Perth metropolitan area has been used as a test case. Two sets of surface albedo and land surface temperature (LST) measurements were taken at different locations on a variety of urban LULC surfaces using two procedures. Firstly, field measurements were made with a pyranometer and a hand-held infrared camera. Secondly, a Landsat 8 image was used to create maps of estimated surface albedo and LST. A new adjustment method was applied to the field measurements to adjust them to satellite overpass time. The results demonstrate that surface albedo and LST are influential factors in determining the thermal characteristics of LULC surfaces. Some built-up areas have a negative effect on the urban environment of Perth compared with non-built-up categories. The correlation between adjusted field work and Landsat 8 data is in strong agreement for surface albedo, and reasonably strong for land surface temperature.